Efficient and reliable detection of rhodamine B using SERS from silver-decorated photonic crystal silicon nanoscale pores - Do Thuy Chi,; Nguyen Thuy Van,; Vu Duc Chinh,; Hoang Thi Hong Cam,; Vilaysak Sayyasone,; Pham Thanh Binh,; Bui Huy,; Pham Van Hoi, (Vietnam Journal of Science and Technology, 2023)
Porous silicon photonic crystal (PSi PhC) decorated with silver nanoparticles (AgNPs) is shown to provide a new substrate for the improvement of SERS. AgNPs are obtained through immersion of PSi PhC samples in AgNO3 solutions and successive thermal annealing. The nanocomposite material generated by adding AgNPs inside the silicon nanoscale pores, integrates the ability of metal surfaces to amplify Raman scattering signals and an enlarged surface area. Besides, PhC structure formed by multilayer PSi increases interaction time of light and matter of the multilayer structure. The experimental results show that the AgNPs-decorated PSi PhC has the largest Raman intensity in comparison with other SERS substrates based on Si. The enhancement of Raman signals also reduces the threshold of the detection down to below 10-10 M. The analytical enhancement factor of AgNPs/PSi PhC SERS substrate for the detection of Rhodamine B (RhB) reaches 1010. This proposed AgNPs/PSi PhC SERS substrate could serve as a potential candidate for detecting RhB in foodstuffs at very low concentrations.